Yamato-74662 Meteorite: A Carbonaceous Chondrite Type II - Yanai, Keizo; Haramura, Hiroshi (1978)
P(論文) Preliminary chemical analysis of Yamato-74662 meteorite suggests that this meteorite belongs to carbonaceous chondrite Type II. No other meteorites of this type have been found among Antarctic meteorites which run to about one thousand. Yamato-74662 meteorite was collected from the surface of bare ice in the Meteorite Ice Field near southern Yamato Mountains, Antarctica on December 30,1974. The bulk chemical composition of Yamato-74662 meteorite in weight % is as follows : 29.18% SiO_2,0.22% TiO_2,2.38% (Al)_2O_3,22.53% FeO, 7.38% FeS, 0.22% MnO, 19.29% MgO, 1.70% CaO, 0.28% (Na)_2O_2,0.04% K_2O, 1.56% H_2O(-), 13.26% H_2O(+), 0.23% P_2O_5,0.85% NiO, 0.52% (Cr)_2O_3,(0.05)_9% Co. departmental bulletin paper